Perbedaan Perilaku Pemenuhan Kebutuhan Spiritual Berdasarkan Tingkat Pengetahuan dan Sikap Pasien Rawat Inap Di Rumah Sakit Raden Mattaher Jambi - Faridah Faridah (Universitas Batanghari Jambi, 2021)
Spiritual needs are very important during the sick period, because when sick, one's energy will decrease and that person's spirituality will be affected, therefore the patient's spiritual needs need to be met. This study aims to determine differences in the behavior of fulfilling spiritual needs based on the level of knowledge and attitudes of inpatients at the Raden Mattaher General Hospital, Jambi. This research is a quantitative analytic study to determine differences in behavior to fulfill spiritual needs based on the level of knowledge and attitudes of inpatients at Raden Mattaher General Hospital Jambi. The research sample was inpatients in the Surgery room. Interne and, Lungs with a treatment duration of more than 1 week. The results showed that the Chi Square analysis showed p-value = 0.001 <0.05, which means that there are differences in the fulfillment of spiritual needs based on patient attitudes and the p-value = 0.036 <0.05, which means that there are also differences in fulfilling spiritual needs based on the patient's level of knowledge. Hospitalization at Raden Mattaher Hospital, Jambi. The patient has a good attitude and high knowledge, so his spiritual needs will be fulfilled as well. It is hoped that the results of this research can be used by the community and especially health workers to pay attention to patients, not only bio, psycho, social needs, but the fulfillment of patients' spiritual needs needs to be considered so that nursing care can be carried out comprehensively.